Level Of Professional Satisfaction Among Doctors And Medical Students Of Bacha Khan Medical College, Mardan - Bilal, Muhammad; Ali shah, Shafqat; Ali Khan, Malik Shayan; Jan, Muhammad Hassan; Hanan, Haseeb; Ali, Sajid; ilyas, Muhammad (Journal of Neonatal Surgery, 2025)
Objective: Assess physician and student burnout and job satisfaction at BKMC/MMC. Analyze the differences in workplace barriers according on designation and gender.Identify the systemic factors affecting career opportunities and mental wellbeing. Study Design: A Cross Sectional Study. Place and Duration of Study. This Cross sectional Study Conducted in Department of Ophthalmology BKMC/MMC from January to March 2025 Method: 218 participants in a cross-sectional research conducted at BKMC/MMC from January to March 2025.employed validated surveys on job satisfaction, burnout, and worries.Data was analyzed using ANOVA (SPSS v26) and t-tests with a significance level of p<0.05. Result: Males were more inclined to remain in Pakistan (p=0.027), whereas females felt less workplace security (p=0.002). Burnout (1.47±0.50) and anxiety about unemployment were highest among medical students (p=0.009).Salary discontent did not differ by gender (p=0.566). Conclusion: At BKMC/MMC, hierarchy and gender have a big influence on job satisfaction. Workplace safety precautions and mental health support are urgently needed.The results are consistent with issues related to physician well-being in resource-constrained environments worldwide.